Anodic Formation of Thick Anatase TiO2 Mesosponge Layers for High-Efficiency Photocatalysis - Lee, Kiyoung; Kim, Dam-Hee; Roy, Poulomi; Paramasivam, Indhumati; Birajdar, Balaji; Spiecker, Erdmann; Schmuki, Patrik (Journal of the American Chemical Society, 2010)
We report a process for the flabrication of an anatase TiO2 mesosponge (TMS) layer by an optimized Ti anodization process in a hot glycerol electrolyte followed by a suitable etching process. Such layers can easily be grown to > 10 mu m thickness and have regular channels and structural features in the 5-20 nm range. The layers show high photocatalytic activity and are mechanically very robust. The layers therefore open new pathways to the wide field of TiO2(anatase) applications.